Let $ f = c$
$ \lim\limits_{h \to 0} \frac{f(x + h) - f(x)}{h} = \frac{c - c}{h} = \frac{0}{h} = 0$
The limit exists and is finite for every $ x \in \mathbb{R}$, so $f$ is differentiable on $\mathbb{R}$ and $f’(x) = 0$
Let $ f = x^n$
$ \lim\limits_{h \to 0} \frac{f(x + h) - f(x)}{h} = \frac{(x + h)^n - x^n}{h} = \frac{x^n + nx^{n-1}h + 2nx^{n - 2}h^2 … h^n - x^n}{h} = \frac{nx^{n-1}h + 2nx^{n - 2}h^2 … h^n}{h}$
$ = nx^{n-1} + 2nx^{n - 2}h … h^{n-1}$, let h = 0
$ = nx^{n-1}$
The limit exists and is finite for every $x \in \mathbb{R}$, so $f$ is differentiable on $\mathbb{R}$ and $f’(x) = nx^{n-1}$.
Let $ f = e^x$
$ \lim\limits_{h \to 0} \frac{f(x + h) - f(x)}{h} =\frac{e^{(x + h)} - e^x}{h} = \frac{e^x (e^h - 1)}{h} = e^x \cdot \frac{e^h - 1}{h}$
$ = \lim\limits_{h \to 0} e^x \cdot \lim\limits_{h \to 0} \frac{e^h - 1}{h} =
\lim\limits_{h \to 0} e^x \cdot 1 = e^x$
$\lim\limits_{h \to 0} \frac{e^h - 1}{h} = 1$, (just trust me on this. its really hard to explain)
The limit exists and is finite for every blah blah blah $f’(x) = e^x$.
Let $ f = \sin x$
$ \lim\limits_{h \to 0} \frac{f(x + h) - f(x)}{h} = \frac{ \sin{(x + h)} - \sin{(x)}}{h} = \frac{ \cos{x} \sin{h} + \sin{x} \cos{h} - \sin{(x)}}{h}$
$ = \frac{ \cos{x} \sin{h}}{h} + \frac{ \sin{x} \cos{h} - \sin{(x)}}{h} = \cos{x} \frac{ \sin{h}}{h} - \sin{x} \frac{(1 - \cos{h})}{h}$
$ = \cos{x} (1) - \sin{x} (0) = \cos{x}$
This works almost exactly the same as the derivative of sine; sub in a cos, the last part of the equation switches and the result if $ - \sin{X}$
Let $ F = (f + g)$
$ \lim\limits_{h \to 0} \frac{F(x + h) - F(x)}{h} = \frac{f(x + h) + g(x + h) - f(x) - g(x)}{h} = \frac{f(x + h) - f(x)}{h} + \frac{g(x + h) - g(x)}{h} = f’ + g'$
Note: The proof for subtraction works exactly the same
Let $ F = (f \cdot g) $
$ \lim\limits_{h \to 0} \frac{F(x + h) - F(x)}{h} = \frac{f(x + h)g(x + h) - f(x)g(x)}{h}$
$ = \frac{f(x + h)g(x + h) - f(x)g(x) + f(x)g(x + h) - f(x)g(x + h)}{h}$
$ = \frac{g(x + h)(f(x + h) - f(x)) + f(x)(g(x + h) - g(x))}{h} = g(x + h) \frac{f(x + h) - f(x)}{h} + f(x) \frac{g(x + h) - g(x)}{h}$
$ = g(x + h) f’ + f(x) g’ = g(x) f’ + f(x) g'$
Let $ F = c \cdot f $
$ \lim\limits_{h \to 0} \frac{F(x + h) - F(x)}{h} = \frac{c \cdot f(x + h) - c \cdot f(x)}{h} = c \cdot ( \frac{f(x + h) - f(x)}{h}) = c \cdot f'$
$ F’ = c \cdot f'$
Let $ F =(\frac{f}{g}) $
$ \lim\limits_{h \to 0} \frac{F(x + h) - F(x)}{h}$
$ = \frac{\frac{f(x + h)}{g(x + h)} - \frac{f(x)}{g(x)}}{h}$
$ = \frac{\frac{f(x + h)g(x) - f(x)g(x + h)}{g(x + h)g(x)}}{h}$
$ = \frac{1}{g(x + h)g(x)} \cdot ( \frac{f(x + h)g(x) - f(x)g(x + h)}{h})$
$ = \frac{1}{g(x + h)g(x)} \cdot ( \frac{f(x + h)g(x) - f(x)g(x + h) + f(x + h)g(x + h) - f(x + h)g(x + h)}{h})$
$ = \frac{1}{g(x + h)g(x)} \cdot (g(x + h) \cdot \frac{f(x + h) - f(x)}{h} - f(x + h) \cdot \frac{g(x + h) - g(x)}{h})$
$ = \frac{1}{g(x + h)g(x)} \cdot (g(x + h) \cdot f’ - f(x + h) \cdot g'$
$ = \frac{1}{g(x)g(x)} \cdot (g(x) \cdot f’ - f(x) \cdot g'$
$ = \frac{1}{g^2} \cdot (f’ \cdot g - f \cdot g'$
$ = \frac{f’ \cdot g - f \cdot g’}{g^2}$
Let $ F = g(f(x))$
$ \lim\limits_{h \to 0} \frac{F(x + h) - F(x)}{h}$
$ \frac{g(f(x + h)) - g(f(x))}{h}$
$ \frac{g(f(x + h)) - g(f(x))}{h} \cdot \frac{f(x + h) - f(x)}{f(x + h) - f(x)}$
$ \frac{g(f(x + h)) - g(f(x))}{f(x + h) - f(x)} \cdot \frac{f(x + h) - f(x)}{h}$
Let t = f(x + h), u = f(x)
$ \lim\limits_{t \to u} \frac{g(t) - g(u)}{t - u} \cdot f’(x)$
$ g’(u) \cdot f’(x) = g’(f(x)) \cdot f’(x)$